Public Health Entrepreneurship in Indonesia: What is Next? - Pratomo, Hadi; Darmawan, Roy; Samaria, Karina (Kesmas, 2025)
Public health has been demanded to search for ways to improve well-being by tackling societal and ecological factors that influence health through cooperative strategies and partnerships across various fields. More interdisciplinary, interprofessional, and action-oriented approaches toward sustainable public health programs are recommended to be made. Therefore, public health entrepreneurship is an indispensable approach to creating new interventions that address future public health problems. The Indonesian Ministry of Health conceptualized five public health entrepreneurship skills as standard competence for public health personnel. In addition, the Association of Indonesian Public Health Higher Education Institutions has identified several study materials and learning outcomes for undergraduate public health personnel. To enrich the currently available approaches, a similar concept of entrepreneurship training, including three course areas: systems of laws and regulations, advertising and public outreach, and financial oversight, consumer insights, and assessment, is presented. The Public Health Entrepreneurship and Intrapreneurship Framework is also presented in this study. Researchers, government, private sectors, experienced entrepreneurs and intrapreneurs, and other stakeholders should collaborate to formulate the best entrepreneurship curriculum for Indonesia. This curriculum can initially be piloted, evaluated, and finally adopted by public health educational institutions in the country.